2017
DOI: 10.1016/j.str.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Phytoene Desaturase Provides Insights into Herbicide Binding and Reaction Mechanisms Involved in Carotene Desaturation

Abstract: Cyanobacteria and plants synthesize carotenoids via a poly-cis pathway starting with phytoene, a membrane-bound C40 hydrocarbon. Phytoene desaturase (PDS) introduces two double bonds and concomitantly isomerizes two neighboring double bonds from trans to cis. PDS assembles into homo-tetramers that interact monotopically with membranes. A long hydrophobic tunnel is proposed to function in the sequential binding of phytoene and the electron acceptor plastoquinone. The herbicidal inhibitor norflurazon binds at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 54 publications
0
61
0
Order By: Relevance
“…Purified proteins, protein complexes, or proteins assembled onto near-native lipid nanodiscs (Efremov et al, 2017;Matthies et al, 2018) can be imaged for structure elucidation. The recent crystal structure determination (Brausemann et al, 2017) for the second enzyme of the pathway, phytoene desaturase, which was found to be active as a homotetramer (Gemmecker et al, 2015), will facilitate structure elucidation of the higher-order oligomeric complexes of the pathway.…”
Section: Solving Structural Mysteries Of the Biosynthetic Machinerymentioning
confidence: 99%
“…Purified proteins, protein complexes, or proteins assembled onto near-native lipid nanodiscs (Efremov et al, 2017;Matthies et al, 2018) can be imaged for structure elucidation. The recent crystal structure determination (Brausemann et al, 2017) for the second enzyme of the pathway, phytoene desaturase, which was found to be active as a homotetramer (Gemmecker et al, 2015), will facilitate structure elucidation of the higher-order oligomeric complexes of the pathway.…”
Section: Solving Structural Mysteries Of the Biosynthetic Machinerymentioning
confidence: 99%
“…This position is equivalent to Leu538 in Oryza sativa . The Leu538 mutations were found to affect the size of the binding pocket (Ala539) of PDS inhibitors in the plant . In addition, the Leu‐256‐Val substitution is a unique and natural mutation in oriental mustard, which has not been identified in the PDS gene of any other species.…”
Section: Discussionmentioning
confidence: 81%
“…The Leu538 mutations were found to affect the size of the binding pocket (Ala539) of PDS inhibitors in the plant. 35 In addition, the Leu-256-Val substitution is a unique and natural mutation in oriental mustard, which has not been identified in the PDS gene of any other species. This clearly shows a critical role of Leu538 in resistance to PDS inhibitors and suggests that the Leu-526-Val (equivalent to Leu538) substitution in the PDS gene identified in this study is likely to be responsible for resistance to diflufenican in the P3 population of oriental mustard.…”
Section: Discussionmentioning
confidence: 99%
“…This position is equivalent to the Leu538 in Oryza sativa which was found to affect the size of the binding site (Ala 539) of PDS‐inhibitors in plants (Fig. ) (discussed in Dang et al …”
Section: Discussionmentioning
confidence: 99%